Analisa Kepatuhan Sustainibility Reporting pada PT Indocement Tunggal Prakarsa Tbk dan PT Semen Indonesia Tbk Berdasarkan Gri Standards dan Iso Aa1000ap pada Tahun 2022 - Prasetyo, Wahyu Heri; Andini, Andini; Haussain Irsyad, Achmad Dias; Holiawati, Holiawati; Ruhiyat, Endang (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The role of the Global Reporting Initiative (GRI) Standards and ISO AA1000AP (AccountAbility Principles) in the context of sustainability reporting stands out as frameworks that serve not only as guidelines but also as key instruments to achieve transparency and consistency in reporting sustainability practices of companies. This research employs a qualitative method with a case study approach to analyze the compliance of sustainability reporting at PT Indocement Tunggal Prakarsa Tbk and PT Semen Indonesia Tbk based on GRI Standards and ISO AA1000AP in 2022. The findings of this study indicate that PT Indocement Tunggal Prakarsa Tbk and PT Semen Indonesia Tbk can strengthen the integrity and quality of their sustainability reporting. This will not only create a greater positive impact but also enhance relationships with stakeholders and ensure sustained engagement with sustainability challenges in the future. Keywords: GRI Standards, ISO AA1000AP, Sustainability Reporting.